Distribution of Hepatitis B prevention services in Wakiso District, Central Uganda. - Tonny Ssekamatte; John Bosco Isunju; Aisha Nalugya; Solomon Tsebeni Wafula; Rebecca Nuwematsiko; Doreen Nakalembe; Winnifred K Kansiime; Naume Muyanga; Joana Nakiggala; Justine N Bukenya; Richard K Mugambe (Public Library of Science (PLoS), 2023)
Hepatitis B Virus (HBV) infection remains a significant global public health challenge especially in low-and-middle income countries. Although there are significant global and national efforts to control Hepatitis B, equitable distribution and access to prevention services such as testing and vaccination remains a challenge. Efforts to increase access are hindered by inadequate evidence on the availability and distribution of HBV services. This cross-sectional study aimed at generating evidence of the distribution of HBV prevention services in Wakiso District, Uganda. A total of 55 healthcare facilities (HCFs) including 4 hospitals, and 51 primary care facilities were surveyed. Data were collected using an electronic structured questionnaire and analysed using STATA 14.0. A chi-square test was performed to establish the relationship between HCF characteristics and the availability of hepatitis B services. ArcGIS (version 10.1) was used to generate maps to illustrate the distribution of hepatitis B prevention services. We found out that the hepatitis B vaccine was available in only 27.3% (15) of the HCF, and 60% (33) had testing services. Receipt of the hepatitis B vaccine doses in the last 12 months was associated with the level (p = ≤0.001) and location (p = 0.030) of HCF. Availability of the hepatitis B vaccine at the time of the survey was associated with the level (p = 0.002) and location (p = 0.010) of HCF. The availability of hepatitis B testing services was associated with the level (p = 0.031), ownership (p≤0.001) and location (p = 0.010) of HCF. HCFs offering vaccination and testing services were mostly in urban areas, and close to Kampala, Uganda's capital. Based on this study, hepatitis B prevention services were sub-optimal across all HCF levels, locations, and ownership. There is a need to extend hepatitis B prevention services to rural, public and private-not-for-profit HCFs.